MENAKAR ULANG HISTORISITAS AL-QUR’ĀN: KRITIK EPISTEMIK ATAS PEMIKIRAN MUHAMMAD ARKOUN - Khairunnisa, Khairunnisa (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines Muhammad Arkoun’s thesis on the historicity of the Qur’an, focusing on its epistemological basis, the historical validity of Qur’anic transmission, and its methodological implications for contemporary Qur’anic studies. Arkoun proposes a fundamental dichotomy between the Qur’an as prophetic discourse and the written muṣḥaf as a historically constructed corpus subjected to canonical closure and interpretive authority. This study employed a qualitative library research design with a critical–interpretive approach and historical verification through classical ʿulūm al-Qur’ān literature and contemporary Qur’anic manuscript studies. The findings showed that: (1) Arkoun’s dichotomy lacks strong transmissional and historical grounding, as Qur’anic preservation has operated through a system of double authentication (oral–written), validated via muʿāraḍah, ḥifẓ, and communal codification (jamʿ tawthīqī); (2) the canonization of the muṣḥaf is more accurately conceptualized as closure by authentication, rather than closure by domination as assumed through Biblical canon-formation analogies; and (3) the core issue in Arkoun’s thesis lies not in the use of historical criticism itself, but in its transformation into an ontological claim that relativizes revelation converting historicity as method into historicity as ontological status. This study emphasizes the need for a critical-constructive framework in Qur’anic studies.